2014
DOI: 10.11138/jts/2014.2.2.081
|View full text |Cite
|
Sign up to set email alerts
|

The use of braces in the rehabilitation treatment of the post-traumatic elbow

Abstract: The elbow, the middle joint of the upper limb, enables the hand to be placed at various distances from the body. The articular, muscular and neuromotor complexity of the elbow is such that it is often prone to stiffness, especially if immobilized for long periods of time. Therefore, mobilization of the posttraumatic elbow must be started early. In the presence of lesions to the ligamentous structures, the joint must be protected to prevent these structures from being placed under tension during movement. Rehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…38 To avoid long-term stiffness, acute pain management guidelines recommend starting mobilization early after trauma. 2,39 Our results indicate that most emergency nurses provided ice packs for patients' acute pain. Similar findings have been reported in intensive care units.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…38 To avoid long-term stiffness, acute pain management guidelines recommend starting mobilization early after trauma. 2,39 Our results indicate that most emergency nurses provided ice packs for patients' acute pain. Similar findings have been reported in intensive care units.…”
Section: Discussionmentioning
confidence: 77%
“…The results of this study showed that nearly all the emergency nurses helped patients with postural care, positioning, and mobilization to reduce their acute pain. Nonpharmacological methods reduced pain significantly 37 and were defined as “therapies that do not involve taking medicines or any other active substances.” 38 To avoid long-term stiffness, acute pain management guidelines recommend starting mobilization early after trauma 2,39 …”
Section: Discussionmentioning
confidence: 99%
“…Again, these splints are timely used for substantial hours in the day. Static progressive braces are preferred because they tolerate biological alteration of the tissue by employing stimulation interchanged with a break [ 11 ]. In the ultimate degrees of flexion, compression forces are employed on the humeroulnar joint, while distraction forces are employed in the ultimate degrees of extension.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its use in rehabilitation treatments, previous research has used a similar device to identify the necessary functional range of motion of the elbow for everyday activities (e.g., Vasen et al, 1995 ). Elbow mobility is essential for upper limb function; a 50% reduction of elbow motion represents ∼80% loss of upper limb function ( Fusaro et al, 2014 ). Stiffness of the elbow is a common occurrence after injury and can be defined as a loss of extension >30° and/or flexion of <120° ( Sojbjerg, 1996 ), and the loss of elbow extension is more frequently encountered than flexion loss ( Charalambous & Morrey, 2012 ).…”
mentioning
confidence: 99%